Differentiation of human pluripotent stem cells into Medial Ganglionic Eminence vs. Caudal Ganglionic Eminence cells - Ahn, Sandra (Methods, 2015)
Human pluripotent stem cells (PSCs) represent an opportunity to study human development in vitro, to model diseases in a dish, to screen drugs as well as to provide an unlimited and ethically unimpeded source of therapeutic cells. Cortical GABAergic interneurons, which are generated from Medial Ganglionic Eminence (MGE) cells and Caudal Ganglionic Eminence (CGE) cells during embryonic development, regulate cortical neural networks by providing inhibitory inputs. Their malfunction, resulting in failure to intricately regulate neural circuit balance, has been implicated in brain diseases, such as schizophrenia, autism and epilepsy. In this study, using combinatorial and temporal modulation of developmentally relevant dorsoventral and rostrocaudal signaling pathways, we efficiently generated MGE cells vs. CGE cells from human PSCs, which predominantly generate Parvalbumin-expressing or Somatostatin-expressing interneurons vs. Calretinin-expressing interneurons, respectively. Efficient generation of specific differentiated progenies of hPSCs as shown in this study will be a pivotal step to realize the full potential of hPSCs for regenerative medicine, developmental studies, disease modeling, bioassay, and drug screening.